Education of fetal movement counting: an effort to increase knowledge and compliance of pregnant women to do self-assessment of fetal wellbeing - Erni Samutri; Lia Endriyani (Alma Ata University Press, 2021)
Background: Decreased movements of the fetus can indicate decrease supply of oxygen and nutrients to the fetus and increase the risk of fetal compromised, even stillbirth. Providing accurate information on fetal movements will help mother to make right decision when dealing with decreased fetal movements. This study aims to determine the effect of fetal movement counting education on knowledge and compliance of pregnant women in performing fetal movement counting.Method: This pre-experimental study allocated 32 pregnant women at 28-37 weeks gestation to practice daily fetal movement counting for 3 weeks. The intervention was a package of fetal movement counting education and practice for 3 weeks. Knowledge on fetal movement counting was measured 4 times by a validated questionnaire and compliance was measured in the end of intervention. Friedman test was used to analyze the changes of women knowledge on fetal movement counting.Results: The results showed that there was an increase in women knowledge on fetal movement counting from 52.94% to 86.10% at the end of intervention, by the highest score in the technihue for fetal movement counting (93.67%). Comparison of 4 measurement periods showed significant changes in knowledge (p <0.000), with a tendency of rise in knowledge. The compliance in performing fetal movement counting was high about 96%.Conclusion: Education of fetal movement counting will increases the knowledge regarding fetal movement. Providing appropriate education and continuous follow-up will increase women’s awareness on the importance of fetal movement monitoring and rise up their compliance to do so.